2018
DOI: 10.1001/jamainternmed.2018.4696
|View full text |Cite
|
Sign up to set email alerts
|

Association of Short Interpregnancy Interval With Pregnancy Outcomes According to Maternal Age

Abstract: IMPORTANCE Interpregnancy intervals shorter than 18 months are associated with higher risks of adverse pregnancy outcomes. It is currently unknown whether short intervals are associated with increased risks among older women to the same extent as among younger women. OBJECTIVE To evaluate whether the association between short interpregnancy (delivery to conception) interval and adverse pregnancy outcomes is modified by maternal age. DESIGN, SETTING, AND PARTICIPANTS A population-based cohort study conducted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
116
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(134 citation statements)
references
References 41 publications
3
116
2
1
Order By: Relevance
“…These observations led to current clinical and public health recommendations advising a minimum IPI of 18 months 9. More recent studies that have matched women as their own controls, to reduce confounding factors, have identified that an IPI <12 months confers greater risk for preterm birth and small for gestational age in high-resource settings, which supports the findings from the previous studies 3 10 11…”
Section: Introductionsupporting
confidence: 72%
“…These observations led to current clinical and public health recommendations advising a minimum IPI of 18 months 9. More recent studies that have matched women as their own controls, to reduce confounding factors, have identified that an IPI <12 months confers greater risk for preterm birth and small for gestational age in high-resource settings, which supports the findings from the previous studies 3 10 11…”
Section: Introductionsupporting
confidence: 72%
“…In a study of women giving birth in Sweden, short interpregnancy intervals (0‐3 months) were not causally associated with increased risk of stillbirth or early neonatal death . A study from British Columbia confirmed the lack of association for women under 35 years but cautioned against short interpregnancy intervals for older women . In low‐ and middle‐income countries where maternal and perinatal mortality and morbidity are high and where women may often start, and end, a pregnancy undernourished and anemic, long interpregnancy intervals may be beneficial.…”
Section: Methodsmentioning
confidence: 99%
“…5 There is little research on modifying interpregnancy inter vals; possible strategies to change such intervals could include educational programmes, cash transfer programmes, and contraception provision programmes, which have been shown to reduce pregnancy rates in LMICs. 6,7 Several studies have examined the association between interpregnancy interval and subsequent adverse perinatal and maternal outcomes, such as small-for-gestationalage birth, 8 preterm birth, 9 low birthweight, 10 child mortality, 11,12 maternal death, 13 and, to a lesser extent, stillbirth. 14 Although many of these studies have found strong associations between short interpregnancy intervals and adverse birth outcomes, there is ongoing debate regarding whether or not the relationship is causal.…”
Section: Introductionmentioning
confidence: 99%